Fibroblast growth factor 2 regulates activity and gene expression of human post‐mitotic excitatory neurons. Issue 3 (27th December 2017) - Gupta, Shweta; M‐Redmond, Tanya; Meng, Fan; Tidball, Andrew; Akil, Huda; Watson, Stanley; Parent, Jack M.; Uhler, Michael
Abstract: Many neuropsychiatric disorders are thought to result from subtle changes in neural circuit formation. We used human embryonic stem cells and induced pluripotent stem cells (hiPSCs) to model mature, post‐mitotic excitatory neurons and examine effects of fibroblast growth factor 2 (FGF2). FGF2 gene expression is known to be altered in brain regions of major depressive disorder (MDD) patients and FGF2 has anti‐depressive effects in animal models of depression. We generated stable inducible neurons (siNeurons) conditionally expressing human neurogenin‐2 (NEUROG2) to generate a homogenous population of post‐mitotic excitatory neurons and study the functional as well as the transcriptional effects of FGF2. Upon induction of NEUROG2 with doxycycline, the vast majority of cells are post‐mitotic, and the gene expression profile recapitulates that of excitatory neurons within 6 days. Using hES cell lines that inducibly express NEUROG2 as well as GCaMP6f, we were able to characterize spontaneous calcium activity in these neurons and show that calcium transients increase in the presence of FGF2. The FGF2‐responsive genes were determined by RNA‐Seq. FGF2‐regulated genes previously identified in non‐neuronal cell types were up‐regulated (EGR1, ETV4, SPRY4, and DUSP6) as a result of chronic FGF2 treatment of siNeurons. Novel neuron‐specific genes were also identified that may mediate FGF2‐dependent increases in synaptic efficacy including NRXN3, SYT2, and GALR1. Since several of these genes have been implicated in MDD previously, these results will provide the basis for more mechanistic studies of the role of FGF2 in MDD. Abstract : Alterations in fibroblast growth factor (FGF) signaling have been implicated in major depressive disorder (MDD). In this article, human stem cells are differentiated into glutamatergic neurons. FGF2 treatment of these neurons increases activity as determined using calcium imaging. RNAseq studies implicate a number of genes in this regulation of neuronal activity by FGF2 including SYT2, NRXN3, and GALR1.